Study of optical properties and molecular structure of plasma polymerized diethylene glycol dimethyl ether - Algatti, M. A. [UNESP]; Mota, Rogério Pinto [UNESP]; Honda, Roberto Yzumi [UNESP]; Kayama, M. E. [UNESP]; Kostov, K. G. [UNESP]; Fernandes, R. S. [UNESP]; Azevedo, T. C. A. M. [UNESP]; Cruz, N. C. [UNESP] (Springer, 2009)
This paper deals with plasma polymerization processes of diethylene glycol dimethyl ether. Plasmas were produced at 150 mtorr in the range of 10 W to 40 W of RF power. Films were grown on silicon and quartz substrates. Molecular structure of plasma polymerized films and their optical properties were analyzed by Fourier transform infrared spectroscopy (FTIR) and ultraviolet-visible spectroscopy. The IR spectra show C-H stretching at 3000-2900 cm(-1), C=O stretching at 1730-1650 cm(-1), C-H bending at 1440-1380 cm(-1), C-O and C-O-C stretching at 1200-1000 cm(-1). The concentrations of C-H, C-O and C-O-C were investigated for different values of RF power. It can be seen that the C-H concentration increases from 0.55 to 1.0 au (arbitrary unit) with the increase of RF power from 10 to 40 W. The concentration of C-O and C-O-C decreases from 1.0 to 0.5 au in the same range of RF power. The refraction index increased from 1.47 to 1.61 with the increase of RF power. The optical gap calculated from absorption coefficient decreased from 5.15 to 3.35 eV with the increase of power. Due to its optical and hydrophilic characteristics these films can be applied, for instance, as glass lens coatings for ophthalmic applications.